Third-Order Fuzzy Subordination and Superordination on Analytic Functions on Punctured Unit Disk - Ekram E. Ali; Georgia Irina Oros; Rabha M. El-Ashwah; Abeer M. Albalahi (Axioms)
This work’s theorems and corollaries present new third-order fuzzy differential subordination and superordination results developed by using a novel convolution linear operator involving the Gaussian hypergeometric function and a previously studied operator. The paper reveals methods for finding the best dominant and best subordinant for the third-order fuzzy differential subordinations and superordinations, respectively. The investigation concludes with the assertion of sandwich-type theorems connecting the conclusions of the studies conducted using the particular methods of the theories of the third-order fuzzy differential subordination and superordination, respectively.